Receipt of Smoking Cessation Medications Among People With and Without Human Immunodeficiency Virus in the Veterans Aging Cohort Study (2003–2018). (20th February 2023) - Shahrir, Shahida; Crothers, Kristina; McGinnis, Kathleen A; Chan, Kwun C G; Baeten, Jared M; Wilson, Sarah M; Butt, Adeel A; Pisani, Margaret A; Baldassarri, Stephen R; Justice, Amy; Williams, Emily C
Abstract: Background: Nicotine replacement therapy, bupropion, and varenicline are smoking cessation medications (SCMs) shown to be similarly effective in people with and without human immunodeficiency virus (PWH and PWoH, respectively), although rates of receipt of these medications are unknown. Methods: We identified patients in the Veterans Aging Cohort Study with electronic health record-documented current smoking using clinical reminder data for tobacco use (2003–2018). We measured receipt of SCMs using Veterans Affairs pharmacy data for outpatient prescriptions filled 0–365 days after current smoking documentation. We used log-linear, Poisson-modified regression models to evaluate the relative risk (RR) for receiving SCM by human immunodeficiency virus (HIV) status, the annual rate of receipt, and rate difference among PWH relative to PWoH. Results: The sample included 92 632 patients (29 086 PWH), reflecting 381 637 documentations of current smoking. From 2003 to 2018, the proportion receiving SCMs increased from 15% to 34% for PWH and from 17% to 32% among PWoH. There was no statistical difference in likelihood of receiving SCM by HIV status (RR, 1.010; 95% confidence interval [CI], .994–1.026). Annual rates of receiving SCM increased for PWH by 4.3% per year (RR, 1.043; 95% CI, 1.040–1.047) and for PWoH by 3.7% per year (RR, 1.037; 95% CI, 1.036–1.038; rate difference +0.6% [RR, 1.006; 95% CI, 1.004–1.009]). Conclusions: In a national sample of current smokers, receipt of SCM doubled over the 16-year period, and differences by HIV status were modest. However, fewer than 35% of current smokers receive SCM annually. Efforts to improve SCM receipt should continue for both groups given the known dangers of smoking. Abstract : Receipt of smoking cessation medications doubled among patients with and without HIV in the VA between 2003 and 2018. Although annual rates of receiving medications were comparable for both populations, there is considerable room for improvement.